FORMULASI CAIRAN PEMBERSIH AIR CONDITIONER (AC) BERBASIS METIL ESTER SULFONAT (MES) - Devy Setyana; Moh Yani; Erliza Hambali (Jurnal Teknologi Industri Pertanian, 2021)
Cleaning is one of the air conditioner (AC) treatments that should be done within a certain period to maintain its function. The AC cleaning process cannot separate from the use of cleaning fluid as one of the main ingredients. This study aimed to obtain the most efficient formulation of AC cleaner fluid from Methyl Ester Sulfonate (MES) with Hydrogen Fluoride (HF) in improving performance and seeing the effect of sonication on the effectiveness of detergent in resulting the AC cleaner. The AC cleaner formulation used the two factors Completely Randomized Design method, namely MES deposition (10%, 20%, 30%) and HF concentration (1%, 2%, 3%). The combination stage was based on parameters of density, viscosity, surface testing, wetting, and pH. From these testers, the three best treatments were M10H3 (MES 10% + HF 3%), M20H3 (MES 20% + HF 3%), M30H3 (MES 30% + HF 3%). Three samples were tested for detergency so that the best treatment was M30H3 (MES 30% + HF 3%). Sonication treatment was able to improve the properties of the resulting AC cleaner, with the density value of 1.0193 g/cm3 to 1,0001 g/cm3 , surface tension from 23.676 dyne/cm to 20.765 dyne/cm, contact angle from 32.37oto 20.5 o, pH from 2.44 to 2.9, and particle size from 10.85 μm to 158.27 nm. The post-state sample had a higher detergency power than before sonication that can increase cleaning ability by as much as 70%. However, the resulting formulation did not have a higher detergency level than commercial AC cleaner brand X.Keywords: AC Cleaner, air conditioner, HF, MES, sonication